Wound management for the advanced practitioner - Swanson, Terry; Asimus, Margo; McGuiness, Bill (IP Communications, 2014)
Increasingly, wound management is recognised as a specialised area of practice. Advances in wound-care products, surgical interventions, and social-support options create an often bewildering array of knowledge for healthcare practitioners. This textbook opens with a focus on the core elements of effective wound management: an understanding of how wounds heal and what inhibits wound healing, rigorous assessment, use of outcome measures, evidence-based approaches to practice, and an understanding of how clinical research is done. Key aspects of wound-bed preparation and management - diagnostic i.